Quality of Service (QoS) improving schemes in optical networks - Hailu, Dawit Hadush; Lema, Gebrehiwet Gebrekrstos; Gebrehaweria, Berihu G.; Kebede, Samrawit H. (Heliyon, 2020)
In optical networks, such as OPS/OBS, the network results into significant loss in the network layer. When the loss significantly deteriorates the QoS by increasing the Bit Error Rate (BER), a viable approach can be used to increase the performance. This paper presents state of the art of Quality of Service (QoS) schemes used for improving the performance of optical networks. Furthermore, some possible applications and performance data are summarized based on Packet Loss Rate (PLR), secrecy, survivability and other parameters. The different states of art methods proposed by several authors are compared with Coded Packet Transport (CPT) scheme. We believe that this study is valuable to researchers envisaging a novel approach to enhance the performance of optical networks for telecommunications networks of the future. Electrical engineering; Computer science; Network (computer science); Computer engineering; Communication system; CPT; OPS; Optical networks; QoS